Building an RPG with Unity 2018 : Leverage the Power of Unity 2018 to Build Elements of an RPG., 2nd Edition. - Karamian, Vahé (Packt Publishing Ltd, 2018)
Unity is one of the most cutting-edge game engines in the world. This comprehensive guide on building some core features of an RPG with Unity teaches you techniques used in developing modern games. The book will mainly focus on the strategy, planning and the implementation of the code. By the end of the book, you will be able to build upon the ...